PENGARUH BRAND LOVE DAN BRAND IMAGE TERHADAP BRAND LOYALTY PADA PRODUK INDOMIE - Wahyuni, Reni Suci (Politeknik Sawunggalih Aji, 2024)
This study aims to test and analyze whether there is an influence of brand love and brand image on brand loyalty of Indomie consumers in Kebumen Regency. Data collection techniques by distributing questionnaires distributed to 100 respondents of Indomie product consumers. The analysis used is validity test, reliability test, classical assumption test, multiple linear regression analysis and coefficient of determination. The data processing tool used is SPSS for Windows version 25.0. The results of this study indicate that: (1) brand love has an influence and is significant on brand loyalty. (2) brand image has an influence and is significant on brand loyalty. (3) brand love and brand image simultaneously affect brand loyalty. The results of the determination coefficient test obtained an Adjusted R Square value of 0.571, meaning that 57.10% of brand loyalty to Indomie products is explained by the brand love and brand image variables while 42.90% is explained by other variables